The expression of the agonistic behavior in Ituglanis ramiroi Bichuette & Trajano 2004 (Siluriformes: Trichomycteridae) and its application for conservation - Monteiro Neto, Diego; Bichuette, Maria Elina (Revista da Biologia, 2018)
Ituglanis ramiroi lives in a special habitat in São Bernardo Cave, mostly upper aquifers fed by infiltration water in the rock. The species was previously studied in relation to reaction to the light; to the spontaneous behavior; to the feeding behavior; and to the locomotor rhythmicity, with evidences of specializations in these behaviors. In the present work, we present the description of agonistic behavior in this species. We verified that the agonistic component was weakly expressed in the tested individuals and could represent a character regression, therefor, a specialization. Specialized behavior in troglobitic species suggests unique evolutionary histories, and must be considered for conservation purpose.